"Mobile (nomadic) cultures" and the politics of mobility: Insights from Indigenous Australia. Issue 4 (23rd April 2018) - Prout Quicke, Sarah; Green, Charmaine
Abstract : The recent "mobility turn" in the social sciences has emphasised the increasing scale and speed of movement in our modern world. It also invites critical analyses of the politics of mobility: how movement is conceptualised and regulated and what these processes reveal about power and marginalisation within societies. However, within this literature to date, there have been relatively few empirical, geographical analyses of mobile (or nomadic) cultures: those peoples whose identities and lived experience are often contested through the interplay of population (im)mobilities and state regulation. Though these mobile cultures – including pastoral nomads, Indigenous hunter‐gatherer peoples and Gypsy/Traveller peoples – are vastly different in many ways, they share a set of common experiences which suggests that an analysis of the politics of mobility for one is likely to have relevance to others. As a call to future comparative efforts, this paper begins by setting out four commonalities across diverse mobile cultures, related to: experiences of oppression; disciplining discourses; forced confinement/sedentarism; and contemporary socio‐economic marginalisation. We then present a set of empirical findings that elaborate the related experiences of one mobile culture in situ. Here, we examine the politics of mobility regulation in the context of Indigenous Australians and state housing policy. The findings reveal how state practices that ignore or attempt to regulate the spatial/population mobilities of mobile cultures have questionable efficacy, and can further entrench the marginal status of mobile cultures. They also show how mobile cultures challenge sedentarist policy parameters that insist on fixity in household tenure and composition. These observed struggles with respect to cultural identity and movement regulation constitute important empirical challenges to the nomadic metaphysics within the mobility turn.